Lunch-Bucket Lives: Remaking the Workers' City - Heron, Craig (Between the Lines, 2015)
Using Hamilton's local history to tell the wider story of the North American working-class, Lunch-Bucket Lives investigates how workers dealt with the profound changes in their lives between the 1890s and the 1930s, as wage-earners, family members, and participants in various social networks. Heron takes wage-earning as a central element in working-class life, but also looks beyond the workplace into the households and neighbourhoods - settlement patterns and housing, marriage, child care, domestic labour, public health, schooling, charity and social work, popular culture, gender identities, ethnicity and ethnic conflict, and politics in various forms - presenting a comprehensive view of working-class life in the first half of the twentieth century. --Publisher's description
Keywords: 19th century; 19th century. Working class; 20th century; 20th century. Social conditions. Working class; Hamilton; Ontario; Social conditions; Working class